The relationship between nutritional status, serum folic acid and homocyteine levels in hemodialysis and peritoneal dialysis patients: Nutritional status, serum folic acid and homocyteine levels - Akalin, Handan; Rakicioğlu, Neslişah (Progress in Nutrition, 2020)
Background. Nutritional deficiencies and imbalances may be encountered in hemodialysis (HD)and peritoneal dialysis (PD) patients. The aim of this study is to investigate the relationship between nutritionalstatus, and serum folic acid and homocysteine levels in hemodialysis and peritoneal dialysis patients.Methods. Information about demographics and eating habits were recorded using a questionnaire in 30hemodialysis and 30 peritoneal dialysis patients. The subjective global assessment was used to assess thenutritional status of the patients. Individual food consumption records were taken in three consecutive days.Some routine blood parameters were recorded from the patient files. Folic acid, vitamin B12 and homocysteineanalysis were also performed from the serum samples from the remaining blood. Results. All of the dialysispatients were found malnourished. Body weight, body mass index, waist and hip circumferences values waslower HD patients than PD patients (p